PENGARUH PENDIDIKAN DAN PELATIHAN, MOTIVASI KERJA SERTA BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN PINRANG - Andi Indriapati; Mashur Razak; Muhammad Hidayat (Nobel Management Review, 2020)
The aim of the research was to determine inThe influence of Education and Training, Motivation and Work Culture on Employee Performance at the Secretariat of the Pinrang Regency Parliament. The method used in the research was quantitative with associative explanative survey study type. The research was conducted in Pinrang regency and the population were employees at the Secretariat of the Pinrang Regency Parliament. The sample was obtained by census technique, which took a total population of 45 employees. Data were analyzed using descriptive analysis techniques and regression analysis to determine the description and influence between variables. This study uses three independent variables namely: education and training (X1), work motivation (X2), and work culture (X3) while the dependent variable is employee performance (Y). The results indicated that the influence of Education and Training, Motivation and Work Culture on Employee Performance at the Secretariat of the Pinrang Regency Parliament. The results of the regression analysis showed a significant influence between the independent variables namely: education and training (X1), work motivation (X2), and work culture (X3) with the dependent variable namely: namely employee performance (Y). The biggest influence occurred on the education and training variable (X1), namely 48.5%, followed by work motivation variable (X2) by 31.8%, and the smallest was the work culture variable (X3) by 28.6%. Simultaneously, there is a significant and positive influence between education and training, motivation and work culture on employee performance at the Secretariat of the Pinrang Regency Parliament by 65.6% while the remaining 34.4% is influenced by other factors that are not the object of research.